تقصّي فعّالية العامل IGF-1 في زيادة الحيوية الخلوية عند الخلايا السرطانية البشرية الكبدية HepG2 - ناصرالدين حسن; عبادي عبد القادر; الحمصي لميس (Latakia University Journal -Biological Sciences Series, 2019)
Insulin like growth factor (IGF-1) is a unique peptide that functions in an endocrine/paracrine and autocrine manner in most tissues. IGF-1 functions as both a circulating hormone and as a tissue growth factor. The binding of IGF1 to its cell surface receptor IGF-1R activates a signaling pathway leading to important physiological aspects in the cell. In this work, we used the human liver cancer cell line HepG2 to test the effects of a homemade recombinant fusion protein sfGFP-IGF-1 on the growth and viability of the cells after treatment with different concentrations. One efficient strategy to extend protein half-life is through recombinant fusion with stable moieties like the green fluorescent protein (GFP). The results show a significant efficacy on the viability of the treated cells by increasing the concentration of the recombinant pure protein sfGFP-IGF-1. The results confirm increasing in gene expression of some target genes using qPCR. The results indicate the significant effect of the recombinant fusion protein sfGFP-IGF̲1 on HepG2 cells viability and on target genes activation. يُعد عامل النمو الشبيه بالأنسولين IGF-1 (Insulin- Like growth factor 1) من الببتيدات الفريدة التي تعمل بعدة طرق endocrine/paracrine and autocrine في معظم الانسجة، اذ تتمثل وظائفه كهرمون جوال في الدم وعامل نمو نسيجي. يؤدي IGF-1 أفعاله من خلال تنشيط التكاثر الخلوي وتثبيط الاستموات الخلوي وذلك بعد ارتباطه بمستقبله الخاص IGF- 1R على أغشية الخلايا ليتم تفعيل شلال الإشارة المؤدي إلى العديد من الظواهر الفيزيولوجية الهامة في الخلية. استخدم الخط الخلوي السرطاني البشري HepG2 لدراسة تأثير البروتين المؤشب المندمج sfGFP- IGF-1 (super folder Green fluorescent protein) المحضّر محلياً في نمو وحيوية الخلايا وذلك بمعالجتها بعدة تراكيز. اذ تكمن إحدى الاستراتيجيات الناجعة في إطالة نصف عمر البروتينات في إنتاجها بشكل مؤشب مندمج مع أجزاء شديدة الاستقرار مثل البروتين الأخضر المتألقGFP . أظهرت نتائجنا قدرة البروتين المؤشب المنقى sfGFP-IGF-1 على زيادة حيوية الخلايا المعالجة بازدياد معامل التركيز. كما أثبتنا حصول زيادة في التعبير المورثي لعدد من المورثات الهدف باستخدام تقنية qPCR بينت هذه النتائج أن البروتين المؤشب المندمج sfGFP- IGF- 1 له تأثير فعال في زيادة حيوية الخلايا HepG2 وتفعيل عدد من المورثات الهدف المسؤولة عن النمو الخلوي.